2009
DOI: 10.1002/app.30693
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of a crosslinked polyelectrolyte membrane for fuel cells with an allyl methacrylate based two‐step reaction

Abstract: In this study, a proton-exchange membrane for fuel cells was prepared via a two-step reaction with an allyl methacrylate (AMA) as an asymmetric crosslinking agent. First, a linear-chain polymer was synthesized, consisting of hydrophilic 2-acrylamido-2-methylpropanesulfonic acid (AMPS), hydrophobic 2,2,2-trifluoroethyl methacrylate (TFEMA), and AMA. Subsequently, we crosslinked the linear-chain polymer by reacting the remaining allyl group during dry heating. The proton conductivity of the prepared membrane was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Examination of the AFM images revealed the presence of light and dark spots, which indicated that the membranes had a phase separation consisting of two types of domains. The light colored spots corresponded to the hydrophilic domains and the dark area depicted the hydrophobic regions [42,43]. It was observed that the hydrophilic domains of pristine membranes BPA-SPAES and 6F-SPAES in Figure 7A, B and E, F, respectively, seemed to be wider and more connected compared with their corresponding crosslinked membranes cr-BPA-SPAES-11 and cr-6F-SPAES-11 in Figure 7C, D and G, H, respectively.…”
Section: Morphology Of the Membranesmentioning
confidence: 87%
“…Examination of the AFM images revealed the presence of light and dark spots, which indicated that the membranes had a phase separation consisting of two types of domains. The light colored spots corresponded to the hydrophilic domains and the dark area depicted the hydrophobic regions [42,43]. It was observed that the hydrophilic domains of pristine membranes BPA-SPAES and 6F-SPAES in Figure 7A, B and E, F, respectively, seemed to be wider and more connected compared with their corresponding crosslinked membranes cr-BPA-SPAES-11 and cr-6F-SPAES-11 in Figure 7C, D and G, H, respectively.…”
Section: Morphology Of the Membranesmentioning
confidence: 87%
“…Numerous copolymers based on the ionizable monomer 2-(acryloylamino)-2methylpropane-1-sulfonic acid (AMPS) or its sodium salt (NaAMPS) and mainly vinyl or acryl comonomers were prepared and characterized because of their various application possibilities (214)(215)(216)(217)(218)(219)(220)(221)(222)(223)(224). Some of them are mentioned in the following text.…”
Section: Poly(sulfonic Acid)s and Their Derivativesmentioning
confidence: 99%
“…The proton conductivity of this membrane is 7 × 10 − 2 S·cm − 1 at room temperature and approaches that of Nafion. The composite membrane material with an enhanced mechanical strength can be produced when the linear chain AMPS-TFEMA-AMA is cross-linked in a fluoroalkyl graft polymer solution (222).…”
Section: Poly(sulfonic Acid)s and Their Derivativesmentioning
confidence: 99%